Capitalist Economics and the Appropriation of Common Resources. Notes from a Democratic Republican Perspective - Baez-Urbina, Francisco Alberto (Sociedad y Economía, 2021)
This article discusses the privatization of institutions that coordinate and regulate the relations of production and distribution between social and economic agents. Through the study of historical sources, a sociopolitical analysis, and political theory, the article aims to contribute to the analysis of the private appropriation of common goods. The conclusions reinforce the argument made by the political economy of democratic republicanism that asserts that the neoliberal capitalist economy is the last stage in the process of private appropriation of common goods.